2019
DOI: 10.1142/s0218001419550164
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model Based on Logistic Regression Algorithm and Extraction Algorithm Using Reward Extremum to Real-Time Detect Blade Icing Alarm

Abstract: Generally, the blades of wind turbine installed in cold regions often encounter the situation of icing on their surface in winter, which affects the performance of wind turbine greatly and reduces power generation. Blade icing of wind turbine is a typical alarm related to multivariates, such as environment temperature, humidity, blade rotation and so on. To successfully achieve a supervised classification, it is necessary to extract the correlated features with blade icing. This paper proposes an extraction al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Oversampling, undersampling, and other sampling methods based on both are recommended to balance the data. Methods to balance the data have been provided in [7,11]. Among the normal data, we first eliminated the icing-free data and then eliminated redundant data.…”
Section: Balancing the Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Oversampling, undersampling, and other sampling methods based on both are recommended to balance the data. Methods to balance the data have been provided in [7,11]. Among the normal data, we first eliminated the icing-free data and then eliminated redundant data.…”
Section: Balancing the Datamentioning
confidence: 99%
“…Wei et al [9] provided features related to the icing of the blades based on practical experience. Li et al [11] proposed a method to identify features correlated with the icing of the blades based on logistic regression and experiments. We use these two studies to extract some features related to icing, as shown in Table 3.…”
Section: Transferring the Featuresmentioning
confidence: 99%
See 1 more Smart Citation